A Beautician’s Dystonia: Long-Lasting Effect of Botulinum Toxin - Siria Di Martino; Stefania Dalise; Giuseppe Lamola; Martina Venturi; Bruno Rossi; Carmelo Chisari (Case Reports in Neurological Medicine)
Treatment options for dystonia are not curative but symptomatic; the treatment of choice for focal dystonias is repeated botulinum toxin injections. Here, we present the case of a 46-year-old beautician with focal dystonia in her left hand that affected her ability to work. Pharmacological treatment with clonazepam and gabapentin failed to resolve her symptoms and was discontinued due to side effects (sleepiness, gastrointestinal disorders). Intramuscular injection of botulinum toxin (incobotulinumtoxinA, Xeomin) into the extensor digitorum communis (35 U), flexor carpi radialis (35 U), and flexor digitorum superficialis (30 U) muscles resulted in complete resolution of symptoms at clinical assessments at 1, 3, 6, and 10 months after the injections, confirmed by the results of surface electromyography 10 months after treatment. The patient was able to work again 1 month after treatment. No reinjection has been necessary at the last evaluation (12 months after treatment). In conclusion, botulinum toxin is an effective treatment for focal dystonia that can have long-lasting effects and can improve patients’ ability to work and quality of life.